VD_FINDINFO Jug / 2014 / 342 vom 13. November 2013 - VD Tribunal cantonal (2013)
FRAIS JUDICIAIRES, INDEMNITÉEN GÉNÉRAL, DÉPENS, HONORAIRES, FAUTE | 426 al. 1 CPP (CH), 426 al. 2 CPP (CH), 429 CPP (CH)